STUDY OF ANTIMICROBIAL ACTION OF EXTRACTS FROM HERB OF TEUCRIUM POLIUM L. (LAMIACEAE) - Y. G. Rudakova; O. I. Papayani; O. I. Popova (Фармация и фармакология (Пятигорск))
Comparative antimicrobial action of Teucrium polium herb extracts using clear water, and 40% and 70% ethanol was examined. The fact that spirit extracts have more conspicuous antimicrobial action was established.